A low-cost GNSS buoy platform for measuring coastal sea levels. (1st May 2020) - Knight, Philip J.; Bird, Cai O.; Sinclair, Alex; Plater, Andrew J.
Abstract: A low-cost Global Navigation Satellite System (GNSS) buoy platform was developed for measuring coastal sea levels to provide information where logistical, physical and/or financial constraints prevent the application of established tide gauges and satellite altimetry, and where spatially and temporally discrete tidal data are required to support surveys for monitoring coastal morphodynamics. The buoy was constructed from scaffold tubing and four floats, with a central platform for the GNSS receiver and antenna. The overall cost was around £300 (buoy parts £100, GPS/logger £200). The single frequency GNSS receiver was set up to record GPS/GLONASS satellite data at 5Hz. Post-processing was carried out with RTKLIB software to derive solutions for sea level. GNSS buoy performance was evaluated against a reference tide gauge using a Van de Casteele test. The RMSE of 1.4 cm, computed from the differences between the GNSS-buoy and reference tide gauge, demonstrates that this low-cost GNSS buoy tide gauge compares well with previous, more expensive GNSS buoys and is suitable for obtaining local-scale coastal sea level data. In addition to providing coastal data at cm accuracy, the results also indicate the presence of high frequency oscillations in the sea level data caused by coastal geometry and wave-induced disturbance. Highlights: A low-cost Global Navigation Satellite System (GNSS) buoy platform has been developed for measuring coastal sea levels. Comparisons with a reference tide gauge show that it performs well, with similar accuracies to more expensive GNSS buoys. Higher frequency data within the sea level solution suggests the presence of harbour and ferry induced oscillations.